2013
DOI: 10.1001/jamasurg.2013.3033
|View full text |Cite
|
Sign up to set email alerts
|

Gallstone Pancreatitis Without Cholecystectomy

Abstract: In patients who did not undergo cholecystectomy, the risk of recurrent pancreatitis is significant. Endoscopic retrograde cholangiopancreatography mitigates this risk and should be considered during initial hospitalization if cholecystectomy is not done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
46
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 18 publications
4
46
1
Order By: Relevance
“…These results are supported by several retrospective studies that also cited significantly higher recurrence rates of gallstone disease (15%-32%) in patients who did not undergo index admission cholecystectomy. [132][133][134] The majority of these recurrent attacks occurred before the time of interval cholecystectomy. 133,134 In an RCT that included 50 patients with mild acute gallstone pancreatitis, laparoscopic cholecystectomy performed within 48 hours of admission resulted in a shorter hospital stay (mean 3.…”
Section: Management Of Acute Gallstone Pancreatitismentioning
confidence: 99%
See 3 more Smart Citations
“…These results are supported by several retrospective studies that also cited significantly higher recurrence rates of gallstone disease (15%-32%) in patients who did not undergo index admission cholecystectomy. [132][133][134] The majority of these recurrent attacks occurred before the time of interval cholecystectomy. 133,134 In an RCT that included 50 patients with mild acute gallstone pancreatitis, laparoscopic cholecystectomy performed within 48 hours of admission resulted in a shorter hospital stay (mean 3.…”
Section: Management Of Acute Gallstone Pancreatitismentioning
confidence: 99%
“…[132][133][134] The majority of these recurrent attacks occurred before the time of interval cholecystectomy. 133,134 In an RCT that included 50 patients with mild acute gallstone pancreatitis, laparoscopic cholecystectomy performed within 48 hours of admission resulted in a shorter hospital stay (mean 3. 135 A second study demonstrated similar findings, with a significant reduction in the mean total length of stay from 7 to 5 days (p < 0.001).…”
Section: Management Of Acute Gallstone Pancreatitismentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, delay of cholecystectomy has been associated with the recurrence of pancreatitis in between 33% and 63% of cases and a higher rate of readmissions (18%) due to complications from the lithiasis (biliary colic, cholangitis, choledocholithiasis) (9)(10)(11).…”
mentioning
confidence: 99%